The Efficiency of Plant Defense: Aphid Pest Pressure Does Not Alter Production of Food Rewards by Okra Plants in Ant Presence - Singh, Akanksha; Mayer, Veronika E.; Zytynska, Sharon E.; Hesse, Benjamin; Weisser, Wolfgang W. (Frontiers in Plant Science, 2021)
Pearl bodies are produced by some plant species as food reward for ants and in exchange, ants defend these plants against insect pests. Sap-sucking pests such as aphids also excrete honeydew as food reward for ants, leading to potential conflict where ants could preferentially defend either the plant or the aphid. How pest insects might influence plant pearl body production, is yet to be investigated. Okra is a widely consumed vegetable worldwide and is attacked by the ant-tended cotton aphid. The plants produce pearl bodies, which are predominantly found on the underside of the leaves and formed from epidermal cells. We conducted a set of field and greenhouse experiments to explore plant-aphid-ant interactions, their influence on pearl body production and resulting performance of okra plants, across okra varieties. We found that ants of Pheidole genus, which are dominant in okra fields, preferred pearl bodies over aphid honeydew; although, their highest abundance was recorded in presence of both these food rewards, and on one okra variety. Removal of pearl bodies from the plants increased their production; however, plant growth and chlorophyll content were negatively associated with pearl body replenishment. Potentially to mitigate this resource cost, plants developed such a novel defence response because we found that aphid presence reduced pearl body production, but only when there were no ants. Finally, aphids negatively affected plant performance, but only at very high densities. As aphids also attract ants, plants may tolerate their presence at low densities to attract higher ant abundances. Our study highlights that plants can adapt their defence strategies in pest presence for efficient resource use. We suggest that understanding pearl body associated interactions in crop plants can assist in using such traits for pest management.